Comparative study of thaumatin protein from Thaumatococcus daniellii grown at different growth environments - Md Zin, Noor Hasniza; Ahmad Radzi, Muhammad Ahsanuddin; Abdul Wahab, Widya; Mohd Khairlani, Nurul Hidayah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2019)
Introduction: This study was carried out to investigate thaumatin profile in Thaumatococcus daniellii fruit cultivated in different growth condition. Methods: Three different samples used were T. daniellii that grown naturally, T. daniellii treated with low fertilizer and T. daniellii treated with high fertilizer. The aril part of the fruit contains intense sweetener protein that can substitute sugar and other artificial sweetener was analaysed by Bradford assay and SDS-PAGE for determination of protein content and differences in protein expression repectively. Results: The total protein concentration of each sample calculated using Bradford assay were 0.367 ± 0.007 μg/μl, 0.343 ± 0.014 μg/μl and 0.426 ± 0.027 μg/μl for T. danielli grown at natural condition (uncontrolled environment), T. daniellii treated with low fertilizer and T. daniellii treated with high fertilizer respectively. All T. daniellii samples showed the presence of thaumatin as shown by the SDS-PAGE image. Only a single band appeared on the SDS-PAGE at the molecular weight of 22 kDa which is the actual size for thaumatin. The band intensity of T. danielli treated with high fertilizer appeared to be highest compared to the other two samples showing high in protein expression. Conclusion: This finding will be useful for other researchers to find out more about this plant for thaumatin production with the best growth condition.